Ruang Lingkup dan Landasan Sumber Filsafat Pendidikan Islam - Asyiroh, Nahdliana Aisyatul; Muhammad Asrori (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to examine the scope and foundation of the source of Islamic educational philosophy by exploring the ontological, epistemological, and axiological dimensions, as well as practical aspects that include educational goals, the role of educators and students, curriculum, methods, and educational environment. This research shows that Islamic philosophy of education has a strategic role as a conceptual framework that directs educational goals, as well as as a normative guideline that affirms the position of revelation as the center of value orientation. The findings of this study confirm that the Qur'an and Hadith are the primary foundations that provide a normative basis for the entire educational process, while ijma', qiyas, scholarly thought, and human intellect and experience serve as secondary sources that allow Islamic education to develop adaptively following social dynamics. The integration of these two sources makes the philosophy of Islamic education comprehensive, flexible, and relevant in responding to contemporary educational challenges, so a deep understanding of the scope and philosophical foundations of this is necessary to strengthen the direction of development of Islamic education and ensure that educational practices remain in harmony with the fundamental values of Islam. In order to explore this philosophical construction, this study uses a qualitative approach with the literature review method; Data were obtained from relevant primary and secondary literature and analyzed using content analysis techniques to identify core concepts and their relevance to the development of Islamic education.